Replication Data for: Recommendation domains to scale out climate change adaptation in cocoa production in Ghana - Bunn, Christian; Quaye, Amos; Läderach, Peter R.D.; Muilerman, Sander; Noponen, Martin; Lundy, Mark M. (International Center for Tropical Agriculture, 2019)
Cacao suitability data for Ghana, baseline (1950 - 2000) and future (2040 - 2069) trajectories. The future trajectory was modeled under an RCP 6.0 climate scenario. (2019-12-17)